Pengembangan Kompetensi Guru dalam Mendesain Pembelajaran pada Kurikulum Merdeka/ Teacher Competency Development in Designing Learning in the Independent Curriculum - Suttrisno Suttrisno; Nurul Mahruzah Yulia (Al-Mudarris: Journal Of Education, 2022)
One of them is to give flexibility and freedom to teachers to design learning that is fun and meaningful. Where the teacher must be able to design, implement and evaluate the learning program independently. The ability to design or design learning is one of the keys to the success of learning goals. In schools, teachers have a role as well as a determining factor in the success of the achievement of learning objectives and to achieve the success of these learning objectives, it takes a good learning design again appropriate. That's why teachers must have the ability to design learning. The objectives of this study include 1) Understanding the concept of Learning design 2) explaining the competence of teachers in designing good learning. The method used in writing this journal is a literature study in which research data obtained from several literary theories are processed and analyzed and then described, so that the results obtained that at the initial stage, teachers must first understand the 5 main components in learning design, as for the five components include learning objectives (general and specific), understanding the learner/student, analyzing Learning, Mastering learning strategies and finally conducting learning evaluation/assessment. The five components can be owned by the teacher if the teacher can develop at least four items of ability contained in the teacher's pedagogical competence related to mastery of curriculum management, student management, academic activity management, and administrative management. All components of the ability must contain the purpose of the free learning curriculum that is realized in the Pancasila student profile strengthening project.